2013
DOI: 10.1103/physreva.88.023850
|View full text |Cite
|
Sign up to set email alerts
|

Quantum limit of laser cooling in dispersively and dissipatively coupled optomechanical systems

Abstract: Mechanical oscillators can be cooled by coupling them to an optical or microwave cavity. Going beyond the standard quantum noise approach, we find an analytic expression for the steady-state phonon number in systems where the position of the mechanical oscillator modulates the cavity frequency as well as the cavity line width. We trace the origin for the quantum limit of cooling to fluctuations in the optical force both at and away from the mechanical frequency. Finally, we calculate the minimal phonon number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 22 publications
2
74
0
Order By: Relevance
“…Note that sideband resolution is not a stringent requirement in optomechanical systems with dissipative interaction, where the oscillator displacement changes the damping rate (or line width) of the optical mode [47][48][49][50][51][52][53][54][55]. Although works on that topic are relatively rare, the predicted cooling has been verified experimentally [51] in an optomechanical system based on the MichelsonSagnac interferometer [50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that sideband resolution is not a stringent requirement in optomechanical systems with dissipative interaction, where the oscillator displacement changes the damping rate (or line width) of the optical mode [47][48][49][50][51][52][53][54][55]. Although works on that topic are relatively rare, the predicted cooling has been verified experimentally [51] in an optomechanical system based on the MichelsonSagnac interferometer [50].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [50] gave another experimental construction involving the Michelson-Sagnac interferometer, which was implemented in experiment very recently [51]. The strong coupling effects [52], cooling limit [53], anomalous dynamic backactions [54], and stabilities [55] associated with dissipative cooling have also been studied recently. However, research on this topic is rare in comparison with the literature on dispersive optomechanics.…”
Section: B Cooling With Dissipative Couplingmentioning
confidence: 99%
“…Dissipative coupling may significantly enhance the detection sensitivity in optomechanically-based sensing schemes [8,9]. Moreover, it could open new possibilities in the optomechanical control of systems featuring both types of coupling mechanisms [10,11], where a tailored coupling strength is highly desirable. Such tailoring was demonstrated using external [3] or integrated [6] variation of the geometry of the optical access channel to the nanocavity.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic dissipative coupling can therefore be controlled externally, deterministically and independently of the other coupling mechanisms. This can lead to a straightforward implementation of optomechanical resonators capable of reaching the optimal mixed coupling ratio in view of achieving an optimal optical cooling of the mechanical mode [11].…”
Section: Introductionmentioning
confidence: 99%
“…This offers as the first crucial step for most applications such as the exploration of quantum-classical boundary [8][9][10] and quantum information processing [11][12][13]. Recently cooling of mechanical resonators has been demonstrated using various approaches including pure cryogenic cooling [14], feedback cooling [15][16][17][18][19] and cavity-assisted backaction cooling [6,7,[20][21][22][23][24][25][26][27][28], along with many theoretical and experimental efforts on novel cooling schemes, such as cooling with dissipative coupling [29][30][31][32][33], quadratic coupling [34], single-photon strong coupling [35], hybrid systems [36,37], laser pulse modulations [38][39][40][41][42] and dissipation modulations [43]. It is theoretically shown that groundstate cooling is possible in the resolved sideband regime [44][45][46], where the mechanical resonance frequency is greater than the decay rate of the optical cavity, indicating the resolved mechanical sideband from cavity mode spectrum.…”
mentioning
confidence: 99%